Phosphorylation of Beta-3 adrenergic receptor at serine 247 by ERK MAP kinase drives lipolysis in obese adipocytes - Shangyu Hong; Wei Song; Peter-James H. Zushin; Bingyang Liu; Mark P. Jedrychowski; Amir I. Mina; Zhaoming Deng; Dimitrije Cabarkapa; Jessica A. Hall; Colin J. Palmer; Hassan Aliakbarian; John Szpyt; et al. (Elsevier, 2018)
Objective: The inappropriate release of free fatty acids from obese adipose tissue stores has detrimental effects on metabolism, but key molecular mechanisms controlling FFA release from adipocytes remain undefined. Although obesity promotes systemic inflammation, we find activation of the inflammation-associated Mitogen Activated Protein kinase ERK occurs specifically in adipose tissues of obese mice, and provide evidence that adipocyte ERK activation may explain exaggerated adipose tissue lipolysis observed in obesity. Methods and Results: We provide genetic and pharmacological evidence that inhibition of the MEK/ERK pathway in human adipose tissue, mice, and flies all effectively limit adipocyte lipolysis. In complementary findings, we show that genetic and obesity-mediated activation of ERK enhances lipolysis, whereas adipose tissue specific knock-out of ERK2, the exclusive ERK1/2 protein in adipocytes, dramatically impairs lipolysis in explanted mouse adipose tissue. In addition, acute inhibition of MEK/ERK signaling also decreases lipolysis in adipose tissue and improves insulin sensitivity in obese mice. Mice with decreased rates of adipose tissue lipolysis in vivo caused by either MEK or ATGL pharmacological inhibition were unable to liberate sufficient White Adipose Tissue (WAT) energy stores to fuel thermogenesis from brown fat during a cold temperature challenge. To identify a molecular mechanism controlling these actions, we performed unbiased phosphoproteomic analysis of obese adipose tissue at different time points following acute pharmacological MEK/ERK inhibition. MEK/ERK inhibition decreased levels of adrenergic signaling and caused de-phosphorylation of the β3-adrenergic receptor (β3AR) on serine 247. To define the functional implications of this phosphorylation, we showed that CRISPR/Cas9 engineered cells expressing wild type β3AR exhibited β3AR phosphorylation by ERK2 and enhanced lipolysis, but this was not seen when serine 247 of β3AR was mutated to alanine. Conclusion: Taken together, these data suggest that ERK activation in adipocytes and subsequent phosphorylation of the β3AR on S247 are critical regulatory steps in the enhanced adipocyte lipolysis of obesity. Keywords: ERK, Beta adrenergic receptor, Lipolysis, Free fatty acid, Obesity, Insulin resistance, Adipose, Fat